2017
DOI: 10.1016/j.kint.2016.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic supplementation in diabetic hemodialysis patients has beneficial metabolic effects

Abstract: This study determined the effects of probiotic supplementation on glycemic control, lipid concentrations, biomarkers of inflammation and oxidative stress in 60 diabetic patients on hemodialysis in a parallel randomized double-blind placebo-controlled clinical trial. Participants were initially matched based on sex, duration of dialysis and diabetes, body mass index and age. Subsequently, they were randomly divided into two groups to take either a capsule containing the probiotics Lactobacillus acidophilus, Lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
179
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(193 citation statements)
references
References 48 publications
10
179
1
3
Order By: Relevance
“…The subgroup analysis of two studies on non‐dialysis patients displayed that probiotic supplements significantly reduced urea (MD = −30.01; 95% CI = [−56.78, −3.25]; P = 0.03), with high heterogeneity ( P = 0.08; I 2 = 68%). In the four studies, on dialysis patients, the subgroup analysis exhibited no significant difference between probiotics and placebo (MD = 0.1; 95% CI = [−9.28, 9.48], P = 0.98), with no heterogeneity ( P = 0.65, I 2 = 0%) (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subgroup analysis of two studies on non‐dialysis patients displayed that probiotic supplements significantly reduced urea (MD = −30.01; 95% CI = [−56.78, −3.25]; P = 0.03), with high heterogeneity ( P = 0.08; I 2 = 68%). In the four studies, on dialysis patients, the subgroup analysis exhibited no significant difference between probiotics and placebo (MD = 0.1; 95% CI = [−9.28, 9.48], P = 0.98), with no heterogeneity ( P = 0.65, I 2 = 0%) (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…In the meta‐analysis, six of the included studies reported the changes in serum creatinine level. Heterogeneity of the six studies was significant ( P = 0.006, I 2 = 69%).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the findings of an antioxidative effect of the synbiotic supplement were in line with previous studies. Soleimani et al showed that probiotic supplementation for 12 weeks among diabetic hemodialysis patients reduced levels of some inflammation biomarkers as well as markers of oxidative stress such as MDA. In another study, consumption of bread containing a synbiotic bread for 8 weeks by patients with T2DM decreased plasma MDA levels; however, it did not affect plasma total antioxidant capacity, glutathione, or catalase levels .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the findings of an antioxidative effect of the synbiotic supplement were in line with previous studies. Soleimani et al 35 showed that probiotic supplementation for 12 weeks among diabetic hemodialysis patients reduced levels of some inflammation biomarkers as well as markers of oxidative stress such as MDA. In another study, consumption of bread containing 36 In the study by Suo et al, it was found that a probiotic supplement containing Lactobacillus fermentum) reduced MDA activity in mice with gastric injury.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its benefits, pharmacotherapy may result in significant side effects including abdominal discomfort, dizziness, diarrhea and hypoglycemia [22]. As research suggests that probiotic interventions may attenuate some of the adverse metabolic effects of type 2 diabetes [23,24], probiotics may also provide an acceptable treatment option in women with GDM.…”
Section: Introductionmentioning
confidence: 99%